Effects of coconut meal inclusion on growth performance, nutrient utilization, carcass characteristics, and meat quality in Awassi Lambs - Ja’far Al-Khaza’leh; Belal Obeidat (Veterinary World)
Background and Aim: Feed cost constitutes a major constraint in small ruminant production systems in Jordan. The search for alternative, cost-effective feed ingredients has prompted interest in coconut meal (COC), a by-product of coconut oil extraction. This study evaluated the effects of including 10% COC (COC10) in the diet on the growth performance, nutrient utilization, carcass characteristics, and meat quality of growing Awassi lambs.